Recyclable and Reusable Catalyst of Chitosan-Modified MgAl-Layered Double Hydroxide for Biodiesel Production - Azlan bin Kamari (Tanjung Malim, 2024)
Recyclable and Reusable Catalyst of Chitosan-Modified MgAl-Layered Double Hydroxide for Biodiesel Production by Azlan bin Kamari